Educational Ceiling in a Rural Tamang Community in Nepal: An Ethnographic Study - Acharya, Laxman (Nepalese Journal of Development and Rural Studies, 2017)
This research study conducted in a rural Tamang community of Nepal aims to explore the real dynamics behind school dropout. The school drop-out is an act of stopping children from going to school after a couple of years of school attainment. A qualitative approach with ethnographic method was adopted to study the school dropout phenomenon. Data were collected over a prolonged stay where observations, in-depth interviews, interactions with research participants and focus group discussions (FGDs) were major data collection tool to understand this phenomenon more closely and to interpret it in relation to culture of the Tamang community. This research claims that various factors related to school, household, parents and children themselves revealed by earlier research studies as cause of school dropout are simply the enabling factors, which in combine, construct a more abstract dynamics, i.e. educational ceiling. The educational ceiling refers to the minimum level of education the people think that they must attain in their life. Actually, this dynamics guides individuals in evaluating the relevance of education in their lives and to take the decision of dropout accordingly. This finding was explored from the cultural artifices of the Tamang community and their way of setting their educational ceiling, employing the inter-actionist approach. This study implies that the scope of the dropout issue is beyond the education system. As and when these individual and society’s contexts change, the educational ceiling of individual also changes and, thus, the dropout scenario changes accordingly. Nepalese Journal of Development and Rural Studies Vol. 14 (Joint issue) (1&2), 2017, Page: 43-55